Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1123/japa.2016-0040
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Intervention Effects on Physical Function Among Community-Dwelling Older Adults: A Systematic Review and Meta-Analysis

Abstract: The purpose of this systematic review and meta-analysis was to determine the effects of supervised resistance and/or aerobic training physical activity interventions on performance-based measures of physical functioning among community-dwelling older adults, and to identify factors impacting intervention effectiveness. Diverse search strategies were used to identify eligible studies. Standardized mean difference effect sizes (d, ES) were synthesized using a random effects model. Moderator analyses were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
52
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 84 publications
(121 reference statements)
9
52
1
7
Order By: Relevance
“…Of note, the simplified reablement program was more effective than multifaceted care intervention at improving muscular strength, balance and mobility (e.g., TUG and HGS). These results are in line with other studies that investigated the effects of physical activity intervention . A meta‐analysis of Chase et al .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Of note, the simplified reablement program was more effective than multifaceted care intervention at improving muscular strength, balance and mobility (e.g., TUG and HGS). These results are in line with other studies that investigated the effects of physical activity intervention . A meta‐analysis of Chase et al .…”
Section: Discussionsupporting
confidence: 91%
“…These results are in line with other studies that investigated the effects of physical activity intervention . A meta‐analysis of Chase et al . investigated the effects of supervised resistance and/or aerobic training physical activity interventions on TUG among community‐dwelling older adults and revealed that interventions were particularly effective among frail participants.…”
Section: Discussionsupporting
confidence: 87%
“…En referencia al TUG en concreto, según Sai et al 27 , es el mejor test de equilibrio para predecir caídas recurrentes. Existen numerosas evidencias científicas conforme los ejercicios de tipo aeróbico involucrando al sistema cardiovascular, así como el entrenamiento de la fuerza muscular, producen mejoras a nivel de la condición física, directamente relacionados con la independencia funcional y por tanto con la prevención de caídas y la calidad de vida, como las recogidas en la revisión y meta-análisis de Chase et al 28 . Por el contrario, el programa basado en ejercicios de BG no tiene como objetivo el trabajo de dichos parámetros físicos, por lo que el estímulo que este supone frente al programa de GM pudo ser muy inferior.…”
Section: Discussionunclassified
“…18 A recent meta-analysis showed significant improvements in older people's "up and go" times when exercise ranging from low to moderate aerobic (walking) to high intensity progressive resistance training was started as an intervention; there was a clear dose effect, and those who were the most frail benefited the most. 19 The prevailing attitude that exercise is for young people while older people should be encouraged to relax needs to be challenged. Physical activity is defined as any bodily movement produced by skeletal muscles that results in energy expenditure, including gardening and walking.…”
Section: Keeping Fitmentioning
confidence: 99%
“…The gap between the best possible level of ability and actual ability can be reduced at any age, 26 no matter how many long term conditions the person may have. 19 The increase in the level of ability may not only restore the person to the ability they enjoyed 10 years earlier, it may make the crucial difference between living well at home or being dependent on social care or residential care.…”
Section: Reducing the Costs Of Social Carementioning
confidence: 99%